Criminal Policy on Prevention and Combating of Espionage Activity in Poland. An Aanalysis Illustrated with the Statutory Amendments Adopted in 2023 - Remigiusz, Rosicki (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2024)
The research problem addressed in the text concerns the criminal policy concerned with preventing and combating espionage offences in Poland in 1998–2023. A criminal policy is understood as a particular form of legal policy, encompassing the programming of anti-crime measures through penalties and other legal measures, criminalisation and decriminalisation regulations, and the deliberate creation of penal provisions. The main objective of the analysis is to juxtapose the previous legislation with the new legal solutions criminalising and penalising further types of espionage, which were introduced in 2023. The consequence of the comparative purpose thus defined is the presentation of an assessment of the new solutions from the perspective of penal policy. The analysis is based on two approaches: the dogmatic and the historical-comparative one. The dogmatic approach focuses on the analysis of the penal law provisions themselves and their interpretation, while the historical-comparative approach juxtaposes the current provisions with the earlier changes following the diachronic perspective. The study aims to answer questions about the differences between the current and previous legislation concerned with the criminalisation of espionage, and to assess the effectiveness of the 2023 amendments. Problem badawczy w tekście dotyczy polityki kryminalnej w zakresie przeciwdziałania i zwalczania przestępstwom szpiegostwa w Polsce w latach 1998–2023. Polityka kryminalna jest rozumiana jako szczególna forma polityki prawa, obejmująca programowanie działań przeciwdziałających przestępczości poprzez kary i inne środki prawne, regulacje dotyczące penalizacji i depenalizacji oraz celowe tworzenie przepisów karnych. Głównym celem analizy jest dokonanie porównania poprzedniego stanu prawnego z nowymi rozwiązaniami prawnymi, kryminalizującymi i penalizującymi kolejne typy szpiegostwa a wprowadzonymi w 2023 roku. Konsekwencją tak przyjętego celu komparatystycznego jest prezentacja oceny nowych rozwiązań w perspektywie polityki karnej. Analiza opiera się na dwóch podejściach: dogmatycznym i historyczno-porównawczym. Podejście dogmatyczne koncentruje się na analizie samych przepisów prawa karnego oraz ich interpretacji, podczas gdy podejście historyczno-porównawcze porównuje obecne przepisy z wcześniejszymi zmianami zgodnie z perspektywą diachroniczną. Badanie ma na celu odpowiedzieć na pytania dotyczące różnic między obecnym a poprzednim stanem prawnym, dotyczącym kryminalizacji szpiegostwa oraz ocenę skuteczności wprowadzonych zmian z 2023 roku.
Polityka kryminalna w zakresie zapobiegania i zwalczania działalności szpiegowskiej w Polsce. Analiza wzbogacona zmianami ustawowymi przyjętymi w 2023 r.
Keywords: criminal policy; offences against the state; espionage; espionage activity; counter-intelligence; polityka kryminalna; przestępstwa przeciwko państwu; szpiegostwo; działalność szpiegowska; kontrwywiad